2017
DOI: 10.1177/1938965517734938
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Dark Side of Closed Networks in Cultural Tourism Clusters: The Importance of Diverse Networks

Abstract: Despite the recognized importance of tourism as an engine of economic growth in developed countries, research on the antecedents of innovation in this sector has been sparse, especially in the context of tourism clusters. Scholars have suggested that social capital is a key determinant of firm innovation in the context of tourism clusters, but empirical evidence has been lacking. The aim of this article is to empirically study the interplay between social capital and innovation in the context of tourism cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 140 publications
(230 reference statements)
0
9
0
1
Order By: Relevance
“…Recent studies have emphasized the importance of relations with external agents for a cluster in the tourism context (Martínez-Pérez and Beauchesne 2017). These studies highlight the contribution of bridging capital to connect firms within a CTC to outside agents, which boosts the development of RIs (Doloreux and Mattson 2008).…”
Section: Hypotheses and Methodologymentioning
confidence: 99%
“…Recent studies have emphasized the importance of relations with external agents for a cluster in the tourism context (Martínez-Pérez and Beauchesne 2017). These studies highlight the contribution of bridging capital to connect firms within a CTC to outside agents, which boosts the development of RIs (Doloreux and Mattson 2008).…”
Section: Hypotheses and Methodologymentioning
confidence: 99%
“…Hartmann () reveals that the innovation of the dark tourism paradigm has spread to the University of Central Lancashire, where the dark tourism research agenda are expanding. Despite the recognized importance of tourism as an engine of economic growth in developed countries, research on innovation within the context of dark tourism remains sparse (Johnston, ; Martínez‐Pérez & Beauchesne, ).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…By constructing a network of scenic spots in Baltimore, Maryland, and evaluating their value and connecting paths, Stienmetz and Fesenmaier (2015) pointed out that the process of destination value creation can be conceptualized as a network formed by the interaction between tourists and destinations [36]. Martínez-Pérez1 and Beauchesne (2018) analyzed the effects of closed networks and diverse networks on firm innovation using a sample of 215 hospitality and tourism firms located in the World Heritage Cities of Spain, and found an inverted-Ushaped relationship between closed networks and firm innovation [37]. Kang et al (2018) analyzed the spatial structure of the Seoul tourist attraction system based on social network analysis technology using spatial statistics and found that a tourism destination can have multiple anchor points (i.e., scenic spots), and the spatial distribution pattern of the central area has a hierarchical structure and varies according to the length of stay [38].…”
Section: Research On the Network Structure Of Scenic Spots In Tourismmentioning
confidence: 99%